Characterizing Genetic Transitions of Copy Number Alterations and Allelic Imbalances in Oral Tongue Carcinoma Metastasis. Issue 12 (19th August 2016) - Morita, Takuma; Uzawa, Narikazu; Mogushi, Kaoru; Sumino, Jun; Michikawa, Chieko; Takahashi, Ken‐Ichiro; Myo, Kunihiro; Izumo, Toshiyuki; Harada, Kiyoshi
Abstract : Primary tumor (PT) heterogeneity can significantly affect the genetic profile of clones at metastatic sites. To understand the mechanisms underlying metastasis, we compared the genetic profile of paired PT and metastatic lymph node (MLN) samples obtained from patients with oral tongue squamous cell carcinoma (OTSCC). Large‐scale genetic profiling was performed on paired PT‐MLN samples obtained from 10 OTSCC patients using high‐density single‐nucleotide polymorphism microarrays. We compared the genetic profile of PT and MLN OTSCC samples to identify common and specific copy number alterations and copy‐neutral loss‐of‐heterozygosity (CN‐LOH). Unsupervised hierarchical clustering analysis indicated that 8 of the 10 PT‐MLN sample pairs formed clusters, indicating that the primary and metastatic tumors were composed of predominantly genetically similar tumor cells. In 6 of the 10 pairs, 8q11.21, 8q12.2‐3, and 8q21.3 gains, and 22q11.23 loss were detected in both the PT and MLN. In addition, 16p11.2 CN‐LOH was identified in 9 of the 10 pairs. Conversely, 20q11.2 gain was only observed in the MLNs of 5 of the 10 sample pairs, indicating that genes in this chromosomal region may play a significant role in OTSCC lymph node metastasis. To confirm this, we investigated the expression of two candidate 20q11.2 genes in a separate patient cohort. The expression of one of these genes, E2F1, was significantly increased during the process of metastasis. This study indicates that additional genetic changes, such as 20q11.2 gain, which encodes the E2F1 gene, can be acquired through clonal evolution, and may be required for the metastatic process. © 2016 Wiley Periodicals, Inc.